Heidelberg bibliography of translations of nonfictional texts [data] - Atayan, Vahram; Dallakyan, Meri; Moretti, Daniele; Weber, Anne (Universität, 2025)
This project, funded by the German Research Foundation, compiles an online bibliography of German translations of nonfictional texts published between 1450 and 1850. It includes translations from English and Dutch, covering topics such as natural sciences, medicine, technology, historical documents, travel reports, and theology. The dataset integrates information from existing bibliographies on Romance-German and Latin-German translations. The resulting comprehensive bibliography spans multiple source languages, including Latin, French, Italian, Spanish, Portuguese, English, and Dutch, and supports research across various disciplines. The project also contributes to Digital Humanities by offering free online access and collaborative tools for researchers.